Self-appointed and Self-taught? Professional Characteristics and Challenges of LSP Teachers in Hungary - Stötzer, Andrea; Bagyura, Márton; Farkas, Éva (English teaching & learning, 2025)
Despite the growing international recognition of Languages for Specific Purposes (LSP), the role and needs of LSP teachers in Hungary remain underexplored. Based on a survey of Hungarian higher education LSP teachers, this study examines their professional characteristics and challenges. The findings reveal that many LSP teachers transition from general language teaching without formal training in their students’ disciplines or LSP-specific methodologies. LSP teaching poses unique challenges, including the significant time required to develop curricula and teaching materials. Beyond preparation, teachers often engage in extensive self-directed learning to acquire specialised content knowledge needed to meet diverse and evolving demands. The study underscores the importance of institutional support, advocating for legal frameworks that recognise that teaching LSP differs from teaching languages for general purposes. The results suggest that it would be crucial to create formal training opportunities, foster collaboration between content specialists and LSP teachers, implement mentorship programmes, and reduce the workload of LSP teachers. This research advocates for establishing LSP teaching as a distinct profession within the Hungarian educational landscape, laying the foundations for future research and contributing to the greater recognition of LSP teaching in national and international contexts. 儘管國際間對專業語文(LSP)的認可與日俱增，但對於匈牙利 LSP教師角色與需求仍未有充分的探究。本研究以匈牙利高等教育LSP教師的調查為基礎，審視他們的專業特質與挑戰。研究結果顯示，許多LSP教師都是從一般語言教學轉型而來，未曾接受過學生相關學科或LSP教學法的正式訓練。LSP教學具有其獨特的挑戰，包含了研發課程和教材所需的大量時間。除準備工作外，教師通常還需進行廣泛的自主學習，以獲得所需的專業學科知識以滿足不同領域多樣且不斷變化的需求。本研究強調行政支援的重要性，倡導承認LSP教學有別於一般語言教學的制度框架。研究結果顯示，提供正式的訓練機會、促進學科知識專家與LSP教師之間的合作、實施師徒計畫，以及減輕LSP教師的工作量至關重要。本研究主張確立LSP教學為匈牙利教育領域中的獨特職業，為未來的研究奠定基礎，並促進LSP教學在國內和國際環境中獲得更廣泛的認可。